High-power broadband mid-IR difference-frequency generation driven by a Tm-doped fiber laser - Heuermann, Tobias; Gaida, Christian; Gebhardt, Martin; Stutzki, Fabian; Jauregui, Cesar; Antonio-Lopez, Jose; Schulzgen, Axel; Amezcua-Correa, Rodrigo; Pupeza, Ioachim; Limpert, Jens; Tu¨nnermann, Andreas (Optics InfoBase Conference Papers, 2018)
We present efficient, ultrabroadband intrapulse difference-frequency generation driven by a Tm-doped fiber laser resulting in an average mid-infrared output power of 450 mW spanning more than one octave (-10 dB width) at a central wavelength of 12 μm.
CRIS-Team Scopus Importer:2023-04-20